Close Up Pada Film Dokumenter Insight Of Batik - Rahmad, Cito Yasuki; Widhiarmoko, Pranomo (Capture : Jurnal Seni Media Rekam, 2015)
The Insight of Batik film departs from concerns about batik. Batik is the result of Indonesian culture that is recognized as World Heritage by UNESCO. However, most of the general public admiration of batik is currently only limited by sheer visual beauty, but behind a piece of batik cloth, there are many values that can be used as a lesson. Documentary is part of an effort to provide additional information, knowledge and understanding of batik to the cultural life and society. Starting from this objective, the documentary film raised three themes of batik, which is about the history, teachings, and intensity human in batik. The third theme is packed into a documentary film with a visual concept that emphasizes on Close Up technique. This technique gives the proximity to the audience through its ability to present the details of the object. Close Up also able to build a dramatization that can convey the intrinsic elements of batik. Through the documentary film with a Close-Up visual concept is expected to provide a deep understanding of batik.Keywords: Documentary, film, batik, and close upÂ